REDUCTION OF REJECTION IN DIESEL FUEL INJECTION PUMPING ELEMENT - Nithin.M.R, Dr.Divakar.H.N, Devaraju.G.R, Srinivas.C.N (International Journal of Research Science and Management, 2015)
Quality has been one of the foremost challenges in the manufacturing industry, various statistical methods (like 8 Discipline steps, DOE, shainin) have been devised to improve quality and customer satisfaction, they also form an eminent part of CIP(Continuous Improvement Process) in BPS(Bosch Production System) this project was carried out in BOSCH INDIA, Bengaluru which is the leading manufacturer in Diesel Fuel Injection Pumps and its components. A Diesel pumping Element incorporating Barrel and Plunger forms a vital part of Diesel Injection pump which is known as heart of diesel pump with mechanical clearance as its important parameter. Analysis was done on leak test and mechanical clearance, the rejections were found to be 20% of total production. Defects with highest percentage internal rejections were found as Head Clearance Less rejections 6.96%, Head Clearance More 6.34% and Sticky 4.38% Rejection in the year 2014. Reason for the causes is investigated and solution is optimized by improving the online Inspection Instrument which is basically controlled by pneumatics.